Curso Básico de FIGMA Parte 1 and 2 - Londoño, Juan Manuel; Zapata, Emmanuel; Bonilla, Melissa; Lopez, Sebastian; Moreno, Manuel; Martinez, Karen (2024)
The DCH team of the Bioversity-CIAT Alliance in Latin America organized a two-session course to strengthen the capacities in the basic management of the Figma software in technicians from partner institutions. In this case, INFOAGRO of Honduras, and the Ministry of Agriculture, Livestock and Food (MAGA) and the Private Institute for Climate Change Research (ICC) of Guatemala. The workshop aimed to teach participants how to modify and update agroclimatic bulletins and reports, combining basic design concepts and practical tools in Figma. In the first session, participants learned the basics of design, became familiar with the Figma interface, and created a simple element as an introduction to future projects. In the second, they carried out exercises on the composition of graphic elements and modified an existing agroclimatic bulletin. As a next step, in 2025, the DCH team will deliver to partners in Honduras and Guatemala a design system with Figma templates ready to be modified. This will allow them to generate agroclimatic bulletins and reports autonomously and with the required frequency.